Inteligência artificial aplicada ao jornalismo organizacional - Santos, Dinomar Miranda dos (2024)
The objective of this research is to investigate and describe the complexity of the process of transforming a judicial decision into a journalistic text. As a result of this investigation, we intend to see the feasibility and propose the implementation of a newsbot, which is the practical application of artificial intelligence in the field of media and journalism, as a Minimum Viable Product (MVP), suited to the specific needs of the Superior Military Court. A bibliographic review using bibliometrics tools is presented, as a crucial step to identify the most cited and influential sources in the proposed field. Through the analysis of keywords and citations, it was possible to map trends and improve the theoretical basis. It is expected that the proposed solution can automate information collection and monitoring, in real time, offering relevant information and generating savings in time and public resources.